High perfomance audio power amplifiers for music performance and reproduction - Duncan, Ben, A.M.I.O.A. (Oxford ; Boston : Newnes, 1996)
Power amplifiers and their performance lie at the heart of audio engineering and provide some challenging problems for the engineer. Ben Duncan's experience, as an audio consultant, analog electronics designer and author, give him an unique insight into this difficult but rewarding field. Linking analog electronics, acoustics, heat and music technology; high-end hi-fi and professional PA and recording studio use; theory, modelling and real-world practice; design and repair; the old and the new, the mainstream and the specialised, this comprehensive guide to power amps is a core reference for anyone in the industry, and any interested onlookers. Ben Duncan is well known to many users of audio power amplifiers around the world, both professional and domestic, through his articles, reviews and research papers on music technology in the UK and US press, and through his part in creating several notable professional power amplifiers. Since 1977, he has been involved in the design of over 70 innovative, high-end audio products used by recording and broadcast studios, on stages, in clubs and by the most critical domestic listeners - as well as creating bespoke equipment for top musicians. Born in London, he has travelled widely but has lived mainly in Lincolnshire, home of his family for over 150 years. He is twice co-author of the book Rock Hardware in which he has chronicled the history of rock'n'roll PA. Reprinted with corrections September 1997 Comprehensive and colourful real-life guide Based on wide experience of audio and music technology Well-known and prolific author in the hi-fi and pro-audio press.
Introduction and fundamentals; Overview of global requirements; The input port; Topologies, classes and modes; Features of the power stage; The power supply; Specifications and testing; Real world testing; Choice, application, installation and set-up; Maintenance and surgery; Appendices; Index.
Includes bibliographical references and index.
Keywords: Audio amplifiers; Power amplifiers; Electronic books